Analisis Penyerapan Tenaga Kerja Provinsi Sumatera Selatan - Leo Budiriansyah (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2017)
This study aims to find out how is the level of employment and the influence of economic growth, investment (domestic investment and foreign investment), and provincial minimum wage affect it in the province of South Sumatra. The analytical tool used is Multiple Linear Regression with data obtained is secondary data that is economic growth, domestic invesment, foreign investment, provincial minimum wage, and number of labor in South Sumatera Province during period 2006-2015. The results showed that the absorption of labor force in South Sumatra during the period 2006-2015 has a fluctuated value. More than 50 percent of the workforce is absorbed in the agricultural sector. The rest is mostly absorbed by the trade and services sectors. Based on the regression result, it is found that economic growth, domestic invesment, foreign investment have a significant and positive effect on employment, while provincial minimum wage also has significant influence but has negative relation to employment in South Sumatera Province.